2022
DOI: 10.2147/ott.s363994
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of 3D Hybrid Spheroids for the Investigation of the Crosstalk Between B-Cell Non-Hodgkin Lymphomas and Mesenchymal Stromal Cells

Abstract: Purpose B-cell non-Hodgkin lymphomas (B-NHLs) are the most common lymphoproliferative malignancy. Despite targeted therapies, the bone marrow involvement remains a challenge in treating aggressive B-NHLs, partly due to the protective interactions of lymphoma cells with mesenchymal stromal cells (MSCs). However, data elucidating the relationship between MSCs and B-NHLs are limited and inconclusive due to the lack of reproducible in vitro three-dimensional (3D) models. Here, we developed and describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…Importantly, any other external elements were entered into the experimental setup to stabilize the patterned structure. These spheroids formed in real time reflected the self-aggregation of lymphoma and stromal cells in the hydrogel culture, as we recently described [19].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Importantly, any other external elements were entered into the experimental setup to stabilize the patterned structure. These spheroids formed in real time reflected the self-aggregation of lymphoma and stromal cells in the hydrogel culture, as we recently described [19].…”
Section: Discussionsupporting
confidence: 54%
“…Given that tumors are composed of multiple cell types, 3D co-culturing increases the complexity of tumor models [15][16][17][18]. We recently established that lymphoma cells and MSCs, when co-cultured on agarose hydrogels, self-aggregate into stabile 3D spheroids [19]. Interestingly, we observed that stromal cells form the core of the spheroid and are evenly surrounded by layered lymphoma cells.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The presence of a stromal population enabled the manipulation and processing of spheroids for histological analyses, because stromal cells are able to produce ECM networks that can both physically trap and biologically attract non-adherent cells. 1,38,40 Furthermore, the stromal component added a higher level of complexity to the model, mimicking the crosstalk that takes place within the microenvironment. Another approach that could be exploited for the generation of more compact models, besides adding ECM-producing cells to the culture, is encapsulation of self-assembling spheroids in hydrogel shells to trap the aggregates in a defined space.…”
Section: Modeling the Lymphoid Microenvironment In 3d For Blood Cance...mentioning
confidence: 99%
“…1,3,37 The creation of a co-culture adding a stromal component is an efficient solution to obtain a more compact and cohesive spheroid. 38,39 Duś-Szachniewicz et al, exploiting a non-adhesive agarose microwell system, developed a 3D model of hybrid spheroids to study the crosstalk between B-cell non-Hodgkin lymphoma and MSC cells. The presence of a stromal population enabled the manipulation and processing of spheroids for histological analyses, because stromal cells are able to produce ECM networks that can both physically trap and biologically attract non-adherent cells.…”
Section: Modeling the Lymphoid Microenvironment In 3d For Blood Cance...mentioning
confidence: 99%